2005
DOI: 10.1521/suli.35.2.146.62878
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Compared to Other Causes of Mortality in Physicians

Abstract: Physicians frequently are early adopters of healthy behaviors based on their knowledge and economic resources. The mortality patterns of physicians in the United States, particularly suicide, have not been rigorously described for over a decade. Previous studies have shown lower all-cause mortality among physicians yet reported conflicting results about cause-specific mortality such as suicide. In this study, we compared all-cause and cause-specific mortality in a sample of physicians to the age-gender matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
5
50
1
2
Order By: Relevance
“…[5][6][7] Many studies have compared physician mortality with that of the general population and have found that, despite having a higher life expectancy and a lower mortality rate from avoidable diseases and various other causes, physicians are more susceptible to suicide. 8 Compared with the rest of the working-age population, doctors have a 2.45-fold higher rate of death by suicide. 6 Depression, addictive behaviors, burnout, and occupational stress have been cited as risk factors for suicide among physicians, 7,9-11 especially among younger doctors.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Many studies have compared physician mortality with that of the general population and have found that, despite having a higher life expectancy and a lower mortality rate from avoidable diseases and various other causes, physicians are more susceptible to suicide. 8 Compared with the rest of the working-age population, doctors have a 2.45-fold higher rate of death by suicide. 6 Depression, addictive behaviors, burnout, and occupational stress have been cited as risk factors for suicide among physicians, 7,9-11 especially among younger doctors.…”
Section: Introductionmentioning
confidence: 99%
“…A study of recognised suicides among doctors showed that for females this was twice that of the general population, but it was lower for males (Hawton et al, 2001). In the USA, suicide was found to be the only cause of death among doctors that was higher than in the general population (Torre et al, 2005). In Scandinavia mortality from suicide was increased among doctors of both genders, particularly deaths due to self-poisoning (Juel et al, 1997).…”
Section: Jenny Firth-cozensmentioning
confidence: 96%
“…Some studies reported lower mortality rates among physicians mainly due to physicians' higher socioeconomic status and better health knowledge (Doll and Peto 2000;Lotufo et al 2001;Doll and Hill 2004;Shin et al 2005;Torre et al 2005), however, medical professionals are also exposed to some specific risk factors, such as the hospital environment, stress, anxiety and possibly depression (Caplan 1994). In addition, physicians' heavy workloads might jeopardize their proficiencies in performing care.…”
Section: Study Populationmentioning
confidence: 99%